The association between sclerostin and incident type 2 diabetes risk: a cohort study. (26th January 2017) - Yu, O.H.Y.; Richards, B.; Berger, C.; Josse, R.G.; Leslie, W.D.; Goltzman, D.; Kaiser, S.M.; Kovacs, C.S.; Davison, K.S.
Summary: Objective: To determine whether sclerostin is associated with fasting glucose, insulin levels, insulin resistance or increased risk of incident type 2 diabetes. Background: Type 2 diabetic patients have a higher risk of fractures. Recent studies suggest sclerostin, a regulator of osteoblast activity, is associated with diabetes. Materials and methods: Sclerostin levels were obtained from 1778 individuals with no history of type 2 diabetes participating in the population‐based Canadian Multicentre Osteoporosis Study (CaMos) cohort. Participants were followed until diagnosis of type 2 diabetes, death or end of the study period (31 December 2013). The relationship of sclerostin with fasting glucose, insulin levels and homoeostatic model assessment‐insulin resistance (HOMA‐IR) was studied in linear regression models. Cox proportional hazards models were used to determine the association of sclerostin levels and the risk of incident type 2 diabetes during a mean 7·5 years of follow‐up. Results: Fasting glucose, fasting insulin levels and HOMA‐IR were weakly correlated with sclerostin levels (Spearman's correlation coefficient: 0·11, P < 0·05; −0·09, P < 0·05; and −0·07, P = 0·02, respectively). Multiple linear regression analyses confirmed a significant association between sclerostin and fasting insulin and HOMA‐IR but no significant association with fasting glucose levels. Sclerostin levels were not found to be significantly associated with the risk of incident type 2 diabetes (HR: 1·30; 95% CI: 0·37–4·57). Conclusions: We observed an association between sclerostin levels with fasting insulin levels and HOMA‐IR, but there was no clear association with type 2 diabetes risk. Further studies are needed to understand the role of sclerostin in type 2 diabetes.